Master of public health: Public health field experience report - Talbott, Joan (My University, 2009)
This past summer Sara McReynolds, DVM, MPH, and I had the opportunity to complete our Public Health Field Experience in South America. We worked under the supervision of David Ashford, USDA APHIS, in cooperation with the Kansas-Paraguay Partners. The goals going into the experience were very broad, intending to introduce us to our disease of interest, foot and mouth disease through the Hemispheric FMD Eradication Program, as well as to learn about public health on both national and international levels. This would involve understanding the differences and challenges of eradication programs versus control programs of FMD in developing countries, looking at the design and implementation of intensive national health programs, and understanding the details of FMD and its epidemiology. Other goals included training and experience in outbreak investigation, disease surveillance and the epidemiologic methods of cross-sectional studies. We also aimed to meet with and learn about various governmental and non-governmental organizations involved in human and animal health. As this experience was international and involved many different agencies, organizations and people, it was not just a goal, but a necessity to be flexible with the plans we had set. We spent the first week in Buenos Aires, Argentina taking an intensive Spanish course. The second week was spent in Rio de Janeiro, where we attended the RIMSA 15 conference and visited PANAFTOSA. However, the majority of our time was spent in Paraguay and the many of the goals established prior to our visit focused on our time in Paraguay. While in Asuncion, Paraguay, we stayed with Marcos Medina, his wife, Delia, and their family. Marcos is a veterinarian who obtained two Masters Degrees at Kansas State University. He is currently a consultant for several ranches and also is the technical advisor to the President of the Association Rural Paraguay (ARP). He has an intimate knowledge of both the agriculture industry and the complex political situation that exists in Paraguay. About half of our time in Paraguay was spent in Filadelfia, one of the largest cities in the Chaco region, working with the veterinarians of the Technical Assistance Fernheim (ATF) of the Cooperativa Fernheim. The Chaco was settled by Mennonites from both Canada and Russia during the late 1920’s and early 1930’s. The Mennonites have developed successful agricultural techniques for dairy, beef and crop production despite the uninviting climate and terrain of the Chaco. Part of their success is due to the cooperatives that were formed quickly after their settlement.
Keywords: USDA APHIS; Foot and mouth disease; Paraguay; FMD Eradication; Chaco region; Cooperative fernheim; Agriculture, Animal Pathology (0476)